Study the Effect of Different additive Levels of Biochar and Carboxymethyl cellulose on some Physical Soil Charactarestics - حمدان, سومر; منى بركات ,; مجد درويش, (Latakia University Journal -Biological Sciences Series, 2023)
A field experiment was conducted in Baksa village (lattakia city) in summer of 2022. With Different levels of Biochar(B) and Carboxymethyl cellulose (CMC) (C0=Control, CMC1=2%, CMC2=4%, B1=2%, B2=4%) was added to a sandy loamy soil in which growing maize crop. The experiment followed a completely randomized design with three replicates for each treatment. At the end of the growing season (after 75-85 days), soil samples were taking from the 0-30 cm depth from each plot for measurement of ( mean weight diameter (MWD), Soil infiltration ,Aggregation , bulk density, and porosity). The results show a gradual significant increase in The stability of the soil texture was improved in compost treatments in which value of MWD reached in CMC2B2treatment 1.6 mm, an increase morale compared to the control with increasing application level of Biochar and carboxymethyl cellulose compared to the control treatment (C0). This led to a significant decrease in bulk density compared to C0 treatment by about (0.06-0.08-0.1-0.13g/cm3) in (CMC1-CMC2-B1- B2) treatment, respectively. Total porosity increased in all treatments receiving Biochar and carboxymethyl cellulose. Furthermore, the results showed soil biochar and carboxymethyl cellulose additions achieved a positive decrease in soil water infiltration at all measurement times. Also, there was a great in the effect of the additions of biochar and carboxymethyl cellulose in decreasing the water infiltration of the soil under all measurement